INTEGRATIVE ACADEMIC SUPERVISION FOR CONTINUOUS TEACHER DEVELOPMENT: A QUALITATIVE STUDY AT SDN KALIMULYA 1 DEPOK - Sari, Bermara Giri Menur; Wasliman, Iim; Mulyanto, Agus; Ghoer, Hilman Farouq (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
The dynamic nature of education requires innovative approaches to teacher professional development that can meet the diverse needs of educators and students. This study investigates the implementation of integrative academic supervision (IAS) at SDN Kalimulya 1, Depok, focusing on promoting teachers' continuous growth and addressing challenges in developing professional identity and pedagogical practice. This qualitative study used semi-structured interviews and thematic analysis to explore teachers' experiences and perspectives on integrative academic supervision. Data were collected from teachers and academic supervisors to assess how IAS contributes to teacher competence, collaboration and reflection. The study also identified challenges related to administrative tasks and institutional support. Findings showed a significant improvement in teachers' confidence and pedagogical competence, with 85% reporting better readiness to implement new learning strategies. Collaborative discussions among teachers increased, with 78% engaging in knowledge-sharing practices. In addition, 88 per cent of respondents felt more connected to their professional community, highlighting the role of IAS in strengthening professional identity. However, 70% of teachers noted difficulties in balancing administrative tasks with professional development activities, indicating the need for systemic support. IAS was found to be a practical framework for promoting teacher growth by encouraging reflective practice and collaboration among teachers. This aligns with the theory emphasising experiential and collaborative learning for continuous professional development. However, institutional barriers, such as administrative burdens, underscore the importance of policy adjustments to create a supportive learning environment. This study concludes that IAS significantly improves teachers' competence, motivation and professional identity. To maximise its impact, educational institutions should address time and resource constraints and strengthen policy frameworks that support professional development. Future research should explore the effectiveness of IAS in broader educational contexts to validate these findings and inform best practices in teacher professional development.